Strategi Pengembangan Penggunaan Blogger pada Analogy Studio dalam Melakukan Reservasi - Annisa salsabilah; Dea henmy nicha; Vigo satria zeli p (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
The influence of technology can change the way of transactions in the business world. Analogy studio is a photo studio located on Jln. M. Hatta, Pasar Ambacang, Padang. Analogy Studio provides a choice of photo categories according to the wishes of its customers. The problem that occurs at this studio is that customers don't want to waste time and energy on reservations. In today's technological developments, photography is developing quite rapidly. From the results of the analysis carried out, the author intends to help with the problems that exist in Analogy Studio by utilizing blogger. With the existence of a website-based photo studio ordering information system, it is hoped that it can simplify the transaction and promotion process. So it can make it easier for studios and customers to make orders directly or online.